2023
DOI: 10.1177/27536130231187368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Distance Reiki Program for Frontline Healthcare Workers’ Health-Related Quality of Life During the COVID-19 Pandemic

Natalie L. Dyer,
Ann L. Baldwin,
Rosemary Pharo
et al.

Abstract: Background Reiki is a biofield therapy which is based on the explanatory model that the fields of energy and information of living systems can be influenced to promote relaxation and stimulate a healing response. Objective To conduct a pragmatic within-subject pilot trial of a remote Reiki program for frontline healthcare workers’ health-related symptoms during the COVID-19 pandemic. Methods Healthcare professionals in the UK (eg, physicians, nurses, and paramedics) were eligible to sign up for a distance Reik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, the remaining studies lacked detailed descriptions of procedures and clear information, leading to an unclear classification. Regarding performance bias, the nature of these trials made blinding of participants or Reiki practitioners challenging [ 23 , 33 35 , 37 , 38 , 40 , 43 ]. However, it is crucial to blind the outcome assessment in Reiki intervention studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the remaining studies lacked detailed descriptions of procedures and clear information, leading to an unclear classification. Regarding performance bias, the nature of these trials made blinding of participants or Reiki practitioners challenging [ 23 , 33 35 , 37 , 38 , 40 , 43 ]. However, it is crucial to blind the outcome assessment in Reiki intervention studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is crucial to blind the outcome assessment in Reiki intervention studies. Nevertheless, four studies reported measures taken for blinding outcome assessment, while for the remaining, it was unclear or not specified [ 23 , 34 , 40 , 43 ]. The assessment of attrition and reporting bias was heavily influenced by these two studies [ 40 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations